2000
DOI: 10.1111/j.1365-2621.2000.tb13594.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ingredients on the Functionality of Fat‐free Process Cheese Spreads

Abstract: Emulsifying salts and hydrocolloids, cook time, cook temperature, and pH were evaluated to characterize their effects on firmness, meltability, and spreadability of fat-free process-cheese spreads. Disodium phosphate and trisodium citrate produced properties closest to those of a full-fat reference cheese, with trisodium citrate providing the most meltability. In all cases, incorporation of hydrocolloids resulted in increased firmness, decreased melt, with varying results on spreadability. Increases in cook ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
2
10

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 7 publications
2
44
2
10
Order By: Relevance
“…The changes in ability to absorb water have also been shown to play a major role in the textural performance of various foods (Fennema 1985) and may have influences on the texture of process cheeses. Overall, it was stated that the influence of pH on cheese texture may function through a number of mechanisms (Swenson et al 2000) Conclusion On the basis of sensory characteristics, physical properties and texture profile analysis of processed cheese made from Mozzarella pre-cheese using three acidulants, citric samples were found to rate superior. Although the acetic acid samples showed more recovery of fat and protein but they were hard and possessed acetic flavour.…”
Section: Effect On Physical Properties Of Processed Cheesementioning
confidence: 94%
See 3 more Smart Citations
“…The changes in ability to absorb water have also been shown to play a major role in the textural performance of various foods (Fennema 1985) and may have influences on the texture of process cheeses. Overall, it was stated that the influence of pH on cheese texture may function through a number of mechanisms (Swenson et al 2000) Conclusion On the basis of sensory characteristics, physical properties and texture profile analysis of processed cheese made from Mozzarella pre-cheese using three acidulants, citric samples were found to rate superior. Although the acetic acid samples showed more recovery of fat and protein but they were hard and possessed acetic flavour.…”
Section: Effect On Physical Properties Of Processed Cheesementioning
confidence: 94%
“…It has also been observed that TSC chelated Ca from colloidal calcium phosphate and dispersed casein; the citrateCa complex remained trapped within the process cheese matrix (Shirashoji et al 2006). Swenson et al (2000) observed that use of TSC in fat-free cheese spreads produced properties closest to those of a full-fat reference cheese and provided high meltability. Increasing the amount of TSC or disodium phosphate from 0.5 to 3 % resulted in increased firmness, decreased melt, and decreased spreadability.…”
Section: Effect On Physical Properties Of Processed Cheesementioning
confidence: 99%
See 2 more Smart Citations
“…This increase may be attributed to two factors: (1) an increase in proteolysis during storage, (Kindstedt et al 2004) and (2) an increase in the conversion of insoluble calcium to soluble calcium, which in turn reduced the strength between casein networks (Feeney et al 2002). Higher meltability in control cheese was possibly due to less proteinprotein interaction owing to more calcium sequestration by trisodium citrate (Swenson et al 2000). Also in a study by Carr et al (2002), it was suggested that according to Hofmeister series, sodium ions have more hydration tendency as compared to potassium which means sodium competes more effectively with protein for existing water and causes higher solubilization of colloidal calcium and in turn higher casein hydration.…”
Section: Functional Changes During Storage Of Pmcmentioning
confidence: 99%